Development of principles for construction of a rational method for formalization the assessment process of the negative impact of the environmental problem on the competitive market - Zhytkevych, Olena (Technology audit and production reserves, 2021)
The object of research is environmental issue, caused by global warming which has negative impact on market. Since, any negative impact is associated with externalities, a market cannot be considered as an efficient market. According to the literature research, market with externalities cannot recover by itself.Thus, one of the most problematic places is the proper identification of the problem related to environmental factors. The identified problem and its impact on a market should be modeled to determine possible negative effects on market participants. Based on the study’s results it is possible to approach the development of alternative solutions to the problem in order to increase economic efficiency. Because environmental factors are dynamic and have significant impact on a market, it is not possible to ignore such a relationship, which can lead to a source of a wide range of dangers.The problem can be attributed to the not studied enough, which, in turn, provides a large field of activity for its further study.One of the productive ways to solve this problem is to perform an economic analysis of the environmental problem as an external problem and develop principles for building a rational method of formalizing the assessing process for the negative impact of environmental problems on the competitive market. This will make it possible to automate the process, which will serve as a basic aspect of developing a plan of further actions.To achieve this aim, the author analyzed the environmental factors caused by climate change and have an impact on the ecosystem and markets. The foundations and needs for a climate policy were also analyzed. The climate policy is designed to improve the situation. The basic principles of constructing a rational method of formalizing the process of assessing the negative impact of environmental problems on the competitive market have been proposed by the author.